(untitled) (REMUNOM, 2024)
This study investigates the bullying suffered by nurses within Basic Health Units in a city in the state of Tocantins, analyzing the factors behind the low reporting of these situations, reviewing the most common types of bullying faced and assessing whether employment relationships and nurses’ lack of knowledge are associated with underreporting. Although bullying has serious impacts on professional life, it is little discussed both in universities and in the workplace. Nurses face various forms of harassment, such as public humiliation and work overload, but many cases go unreported due to fear of retaliation or lack of knowledge about how to report it. The survey of 44 primary care nurses used a qualitative and quantitative exploratory field approach. During the survey, it was observed that the majority of those interviewed (45.5%) chose not to report the situations of bullying they had faced. However, it is crucial to promote training and support for nurses to recognize and report bullying, in addition to implementing more robust organizational and government policies to prevent and combat this practice, aiming for healthier and more respectful working environments. Keywords: Moral Harassment. Nurses. Basic Health Units.